Phosphate limitation alleviates the inhibitory effect of manganese on itaconic acid production by Aspergillus terreus. (March 2019) - Saha, Badal C.; Kennedy, Gregory J.
Abstract: Lignocellulosic biomass has the potential to serve as a low-cost source of sugars for production of itaconic acid (IA, a building block platform chemical) by fermentation with Aspergillus terreus . However, the IA production from biomass hydrolysate was severely inhibited. Mn 2+ was found to inhibit the IA production strongly. The effect of Mn 2+ on each medium component (KH2 PO4, NH4 NO3, MgSO4 ·7H2 O, CaCl2 ·2H2 O, FeCl3 ·6H2 O, ZnSO4 ·7H2 O, and CuSO4 ·7H2 O) was evaluated for sugar utilization and IA production by A. terreus NRRL 1972. Both K + and PO4 −3 were necessary for IA production. Low PO4 −3 in the medium greatly alleviated the inhibitory effect of Mn 2+ on IA production. However, high PO4 −3 (K + ) was detrimental for IA production in the presence of Mn 2+ . The inhibitory effect of Mn 2+ on IA production was partly eliminated by increasing the CuSO4 ·7H2 O level in the medium. This is the first report on the effect of phosphate limitation to alleviate the inhibition of IA production by Mn 2+ and on the relationship of Mn 2+ on the medium components for utilization of sugar and production of IA. Highlights: Mn 2+ severely inhibited the production of itaconic acid by Apergillus terreus NRRL 1972. Both K and phosphate were necessary for itaconic acid production by the fungal strain. Low phosphate level was needed to alleviate the inhibitory effect of Mn 2+ . Inhibitory effect of Mn 2+ was partially removed by increasing CuSO4 concentration. Interactions of Mn 2+ with medium components on itaconic acid production were studied.